Flexible product development - Smith, Preston G (Jossey-Bass, 2007)
Includes bibliographical references (pages 267-272) and index.; Flexible Product Development is a hands-on resource thatprovides the tools and strategies needed to restore flexibility toany organization and remove the obstacles that stand in the way ofresponsive new product development. Preston Smith introducesapproaches that can enhance development process flexibility bycreating and maintaining development options, delaying decisions,and, in general, reducing the cost of change. Step-by-step, heexplains the basics of flexible product development, provides abroad array of flexibility-enhancing tools, and guides the readerin modifying the organization?s values to embrace this new way ofoperating.